Estudo de comunidades de dípteros necrófagos sob o formalismo de biclusters e árvores de decisão - Souza, Caroline Rodrigues de [UNESP] (Universidade Estadual Paulista (Unesp), 2016)
The pattern recognition in ecological communities is one of the most antique and persistent challenges of ecological science. In this sense, through mathematical modelling from graphs, using biclusters and decision trees, the objective of the present work was to find patterns in the occurrence of necrophagous dipterans collected in three different areas (rural, urban and forest) and with three different baits (sardines, liver and beef) in the city of Rio Claro-SP. Algorithms (InClose and RInClose-biclusters, C 4.5-decision trees) were used to obtain the results. Through the analysis of biclusters, it can be highlighted those that related Atherigona orientalis (Schiner) and Musca domestica Linnaeus in all environments, less forest area, probably due to the fact of being species known for their preference for areas inhabited by humans. On the other hand, even being species possessing high dependence by antropobiocenose, other biclusters indicated an association between Lucilia eximia (Wiedemann) and Chrysomya megacephala (Fabricius) occurring with greater frequency in the forest, attracted by the bait of meat or liver, both known for their importance in the attractiveness of calliphorid fly. This may be explained due to the population growth occurred around the forest, giving the characteristics of place inhabited by man. With regard to decision trees, were obtained in total 19 decision trees (8 to the family Sarcophagidae, 4 for Muscidade and 7 to Calliphoridae) and from them various patterns can be detected such as: A. orientalis, Synthesiomyia nudiseta (Wulp, 1883) and M. domestica being present together if the season is Spring, the bait is sardines and the location is urban. Oxysarcodexia thornax (Walker) was the only specie in which to achieve the condition of presence, it is necessary to walk only one node (the spring), therefore, it was considered to be generalist in this study, since the local variables and bait were indifferent to determine this location. For all that, it was considered that the decision trees and biclusters are useful tools in the elucidation of existing relationship patterns between the community of dipterans collected.

O reconhecimento de padrões em comunidades ecológicas é um dos mais antigos e persistentes desafios da ciência ecológica. Nesse sentido, através da modelagem matemática a partir de grafos, utilizando biclusters e árvores de decisão, buscou-se encontrar padrões na ocorrência de dípteros necrófagos coletados em três diferentes áreas (rural, urbana e mata) e com três diferentes iscas (sardinha, fígado e carne moída) na cidade de Rio Claro-SP. A partir dos algoritmos (InClose e RInClose – biclusters, C4.5 – árvores de decisãoatravés da análise dos biclusters, podemos destarcar, por exemplo, aqueles que relacionaram Atherigona orientalis (Schiner) e Musca domestica Linnaeus em todos os ambientes de coleta, menos na área de floresta, provavelmente devido ao fato de serem espécies conhecidas por sua preferência por áreas habitadas pelo homem. Por outro lado, mesmo sendo espécies que possui alta dependência pela antropobiocenose, outros biclusters indicaram uma associação entre Lucilia eximia (Wiedemann) e Chrysomya megacephala (Fabricius) ocorrendo com maior frequência na floresta, atraídas pelas iscas de carne ou fígado, já conhecidas pela sua importância na atratividade de califorídeos. Isso pode ser explicado devido ao crescimento urbano ocorrido ao redor da floresta estudada, dando-lhe características próprias de local habitado pelo homem. No que se refere às árvores de decisão, foram obtidas no total 19 árvores de decisão (sendo 8 para a família Sarcophagidae, 4 para Muscidae e 7 para Calliphoridae) e a partir delas pode-se detectar vários padrões como: A. orientalis, Synthesiomyia nudiseta (Wulp, 1883) e M. domestica estando presente conjuntamente se a estação for Primavera, a isca for sardinha e o local for Urbana. Oxysarcodexia thornax (Walker) foi a única espécie, que para atingir a condição de presença, percorreu somente um nó, a estação Primavera, sendo, portanto, considerada generalista neste estudo, já que as variáveis local e isca foram indiferentes para determinar sua localização. Por tudo isso, considerou-se que os biclusters e as árvores de decisão são ferramentas úteis na estimativa de padrãona relação existentes entre a comunidade de dípteros necrófagos.
The study of communities of dipterans scavengers under the formalism of graphs and decision trees
Keywords: Sinantropismo; Moscas; Synanthropism; Flies; Anthropic environments; Ambientes antrópicos